2018
DOI: 10.1038/s41598-018-33832-x
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of neuropathic pain in the back region in chronic low back pain patients -a multicenter investigation

Abstract: Neuropathy can contribute to low back pain (LBP) in the region of the back. Our study investigated the proportion of neuropathic pain (NP) in low back region in chronic LBP patients from multicenter and clinics in China and identified associated factors. Assessment was made using a questionnaire and the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS, only tested in low back region), as well as Quantitative Sensory Testing (QST, merely applied to the low back region), the Hospital Anxiety and Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…To explore the biological relevance of the pQTLs, we carried out colocalisation analysis with neuropsychiatric traits using data published by the Psychiatric Genomics Consortium (PGC), as well as other neurodegenerative traits, using publicly available summary statistics from recent large GWAS meta-analyses (Supplementary Data 5b ). We also studied colocalisation with signals for pain-related traits that have been proven to have a neuropathic component, such as chronic back pain 22 and osteoarthritis 23 . A total of 15 protein–trait pairs colocalised with human disease signals, suggesting a role for the protein in mediating disease.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the biological relevance of the pQTLs, we carried out colocalisation analysis with neuropsychiatric traits using data published by the Psychiatric Genomics Consortium (PGC), as well as other neurodegenerative traits, using publicly available summary statistics from recent large GWAS meta-analyses (Supplementary Data 5b ). We also studied colocalisation with signals for pain-related traits that have been proven to have a neuropathic component, such as chronic back pain 22 and osteoarthritis 23 . A total of 15 protein–trait pairs colocalised with human disease signals, suggesting a role for the protein in mediating disease.…”
Section: Resultsmentioning
confidence: 99%
“…Many independent risk factors for NP in CLBP were reported from previous studies, including advanced age 4,7 , female gender 4,7,14 , male gender 9 , pain intensity 9,14 , diabetes mellitus 4,7 , lumbar, abdominal, or pelvic surgery 7,23 , alcohol consumption 23 , Caucasian race 7 , and smoking. 7 The present study found only advanced age to be an independent risk factor for NP, which is consistent with the results of studies conducted by El Sissi, et al 4 and Kaki, et al 7 A review of the literature is shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a prevalence of NP in CLBP that ranged from 1.6% to 80%. 4,[11][12][13]22,23 The wide range of reported prevalence may be explained by differences in sample size, differences in the reference scores and/or type(s) of questionnaires used, and differences in the locations of pain.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the different signs and symptoms of CLBP might be the involvement of nociceptive and neuropathic pain components (Baron et al., 2016; Bogduk, 2009, IASP Terminology—IASP, n.d.). The stated frequency of neuropathic components in CLBP varies from 2.5% to 54.7%, but strongly depends on the used assessment criteria, assessment tools and investigated patient clientele (Freynhagen et al., 2006; Kaki et al., 2005; Li et al., 2018). Neuropathic pain components in CLBP might have an additional negative influence on the responses to treatments and reduce the quality of life to a greater extent (Beith et al., 2011; Hiyama et al., 2015).…”
Section: Introductionmentioning
confidence: 99%